Silver Ångstrom‐Particles: Ångstrom‐Scale Silver Particles as a Promising Agent for Low‐Toxicity Broad‐Spectrum Potent Anticancer Therapy (Adv. Funct. Mater. 23/2019). (5th June 2019) - Wang, Zhen‐Xing; Chen, Chun‐Yuan; Wang, Yang; Li, Fu‐Xing‐Zi; Huang, Jie; Luo, Zhong‐Wei; Rao, Shan‐Shan; Tan, Yi‐Juan; Liu, Yi‐Wei; Yin, Hao; Wang, Yi‐Yi; He, Ze‐Hui; et al.
Abstract : In article number1808556, Hui Xie and co‐workers report an Ångstrom‐scale silver particle fabricated by a novel evaporation–condensation physical system as an intravenous cancer treatment drug. The Ångstrom‐scale silver particle potently inhibits the growth of multiple cancer cells in vitro and cancer xenografts in nude mice, without inducing notable toxic effects on the healthy cells and tissues. The authors thank Mr. Hong‐Chao Zhan and Miss. Yun‐Xia Chen for their help with the design.